Monitoring Kesehatan pada Tanaman Eucalyptus (Eucalyptus urograndis) Di PT. Industrial Forest Plantation (IFP) Kabupaten Kapuas Kalimantan Tengah: Eucalyptus Health Monitoring (Eucalyptus urograndis) at PT. Industrial Plantation Forest (IFP), Kapuas District, Central Kalimantan - Novi Astri; Eritha Kristiana Firdara; Reri Yulianti (HUTAN TROPIKA, 2022)
This study aims to determine the value of the Eucalyptus health index (Eucalyptus urograndis) and to determine the supporting factors that affect the severity of Eucalyptus (Eucalyptus urograndis) damage. The research method used was Forest Health Monitoring (FHM). The results obtained were the part that had the highest amount of damage was found in the leaves with a percentage of 96.39% damage caused by pests and diseases. The worst part is the next part of the branch with a percentage of 2.66% where the branch is broken due to strong winds. The lowest part of the damage was found in the lower and upper stems which experienced stunted growth (stunted) with a percentage of damage of 0.95%. The cause is due to lack of nutrients and low water absorption, which causes plants to become stunted or experience stunted growth. The value of the eucalyptus health index at PT Industrial Forest Plantation (IFP) is still classified in the healthy class where the average value of the damaging weight is less than 5